SISTEM INFORMASI LOKASI SEKOLAH-SEKOLAH DI KALIMANTAN TENGAH MENGGUNAKAN DELPHI XE2 - Widiatry, Widiatry; Licantik, Licantik; Sutrisno, Achmad (Universitas Palangka Raya, 2015)
One of the facilities are not owned by the Lembaga Penjamin Mutu Pendidikan (LPMP) CentralKalimantan is a system that can be used to find the location of the existing schools in the province ofCentral Kalimantan. The weakness of the absence of this system is the difficulty in establishing a newschool and finding the location of the schools are located in remote areas. By looking at the difficultiesencountered, it would require a computer system which has the ability to build, store, manage and displayinformation schools, for example, data identified according to location, in a database. With thisinformation system is expected to facilitate the implementation of activities in LPMP.The research was made consisting of stages, namely the collection and analysis of data is done bymeans of literature study and observation and for the development of software implementing the waterfallmethod. Implementation of the system is done with Delphi XE2, the database used is Microsoft Access2007.To make the system location information schools in Central Kalimantan is the waterfallmethodology with phase analysis system to determine access rights along with the existing facilities,systems modeling using the Unified Modeling Language (UML) and data modeling using the EntityRelationship Diagram (ERD ), the design of systems with database design, interface design, design schoollocation search, and the appearance of the search results, and system testing using blackbox testing. Todisplay the search results by using the location of the school is an additional application that is API(Application Programming Interface) from google maps to be displayed into the application that createdand we can give the coordinates into the google maps